Perancangan Aplikasi Smartdesa Pada Desa Sipispis Berbasis Mobile - Dian El Arafiah Saragih; Samsudin; Aninda Muliani (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
Research has been carried out in Sipispis Village which is located in Serdang Bedagai Regency. Sipispis Village with a population of ±1,553 people, consisting of 737 men, 816 women and 391 families belonging to 7 (seven) hamlets. For village governance matters, such as letter submission services, they still use a manual system. Apart from the fact that the system is still running manually, the people of Sipispis Village do not get enough information about village news. This is because the village government does not provide a special platform for village news. Complaints from the community about the village cannot be conveyed widely because of the limited system that runs in the village. Therefore, a Smartdesa application system is needed so that it can overcome these problems, for example in community affairs to the village government such as submitting land cover letters, introduction to marriage certificates, acknowledgment of death certificates and certificates of incapacity, domicile letters, introduction to inheritance certificates, introduction to SKCK, birth certificate introduction, and business letter introduction. The required information was collected using a qualitative survey method, namely through observation, interviews and literature studies. The Waterfall method is used in system development. The Smartdesa application can make Sipispis Village governance better and can support village progress.